Expression of the Plasmodium falciparum Clonally Variant clag3 Genes in Human Infections. (7th February 2017) - Mira-Martínez, Sofía; van Schuppen, Evi; Amambua-Ngwa, Alfred; Bottieau, Emmanuel; Affara, Muna; Van Esbroeck, Marjan; Vlieghe, Erika; Guetens, Pieter; Rovira-Graells, Núria; Gómez-Pérez, Gloria P.; Alonso, Pedro L.; D'Alessandro, Umberto; et al.
Summary: Many important Plasmodium falciparum genes show clonally variant expression, but little is known about how these genes are used during human malarial infections. This article reports the expression in human infections of the clonally variant clag3 genes linked to solute uptake. Abstract: Background: Many genes of the malaria parasite Plasmodium falciparum show clonally variant expression regulated at the epigenetic level. These genes participate in fundamental host-parasite interactions and contribute to adaptive processes. However, little is known about their expression patterns during human infections. A peculiar case of clonally variant genes are the 2 nearly identical clag3 genes, clag3.1 and clag3.2, which mediate nutrient uptake and are linked to resistance to some toxic compounds. Methods: We developed a procedure to characterize the expression of clag3 genes in naturally infected patients and in experimentally infected human volunteers. Results: We provide the first description of clag3 expression during human infections, which revealed mutually exclusive expression and identified the gene predominantly expressed. Adaptation to culture conditions or selection with a toxic compound resulted in isolate-dependent changes in clag3 expression. We also found that clag3 expression patterns were reset during transmission stages. Conclusions: Different environment conditions select for parasites with different clag3 expression patterns, implying functional differences between the proteins encoded. The epigenetic memory is likely erased before parasites start infection of a new human host. Altogether, our findings support the idea that clonally variant genes facilitate the adaptation of parasite populations to changing conditions through bet-hedging strategies.